“Association of Parental Education with Frequency of Dental Caries in Mal-Occluded Teeth among 3 11 Years old Children” - Adeel Haidar, Hira Shafique, Gul Muhammad Shaikh, Mehwish Munawar, Attique Ur Rehman, Muhammad Waheed Azfar, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study aimed to explore the association of parental education with frequency of dental caries in mal-occluded teeth among 3- 11 years old children Method: This analytical cross-sectional study was conducted at Dental hospital of Institute of dentistry of a tertiary care hospital of Lahore. Data was collected from 250 patients having dental caries with mal-occluded teeth using purposive sampling technique. For data analysis SPSS version 25.0 was used. For gender and educational categories, frequency and percentages were calculated whereas to explore the impact of parental education on the occurrence of dental caries among children of 3-11years with dental malocclusion, chi-square was used. Result: Results of chi-square revealed that parental education has a significant impact on dental caries occurrence among children having maloccluded teeth (P=0.037). 30(71.43%) children with maloccluded teeth has dental caries parents of whom were having post-graduation degree. 68(66.67%) children with maloccluded teeth has dental caries parents of whom were having graduation degree. 28(70%) children with maloccluded teeth has dental caries parents of whom were diploma holders. 6(50%) of children with maloccluded teeth has dental caries parents of whom were having high school education. Only 37(75%) children with maloccluded teeth has dental caries whose parents had education till middle school. 1(11.11%) children with maloccluded teeth has dental caries whose parents had education till primary school whereas 10(100%) children with maloccluded teeth has dental caries whose parents were illiterate. Conclusion: Oral health of children needs additional attention by introducing more programs dealing with oral health preventive measures which will be helpful in reducing the prevalence of dental caries.